2006
DOI: 10.1519/r-19955.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Competitive Wrestling Season on Body Weight, Hydration, and Muscular Performance in Collegiate Wrestlers

Abstract: The purpose of the present investigation was to examine the effects of a collegiate wrestling season on body weight, hydration, and muscular performance. Twelve Division I collegiate wrestlers (mean +/- SE; 20.75 +/- 0.41 year) volunteered to participate in testing sessions during midseason and 3 weeks following the season. Testing consisted of weigh-in, providing a urine sample for hydration analysis, and a measure of isometric leg extension peak torque. Weight significantly increased (p < 0.05) following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Kraft, Webster, Yoshida, et al [4,[40][41][42][43] showed that power, maximum anaerobic power, vertical jump, vertical ground reaction impulse, body power and mean power have impacted during acute dehydration. The finding of this study disagree with previous studies [41,[44][45][46], which showed that there were no significant effect in peak power, mean power and vertical jump. Reasons of these differences in results were in level of dehydration, mode of testing and mode of measuring power.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Kraft, Webster, Yoshida, et al [4,[40][41][42][43] showed that power, maximum anaerobic power, vertical jump, vertical ground reaction impulse, body power and mean power have impacted during acute dehydration. The finding of this study disagree with previous studies [41,[44][45][46], which showed that there were no significant effect in peak power, mean power and vertical jump. Reasons of these differences in results were in level of dehydration, mode of testing and mode of measuring power.…”
Section: Discussioncontrasting
confidence: 99%
“…Precision was also nearing with a negative effect. Buford et al [46] reported that dehydration was damaging muscle performance. For this study, the authors calculated peak torque in at the knee midseason and postseason in wrestlers.…”
Section: Discussionmentioning
confidence: 99%
“…This theory was strengthened by the fact that all data in literature came from athletes well-familiarised with competing after reducing weight rapidly. Although compelling evidence for adaptation has never been demonstrated, it has been speculated that it could be related to the increased ability to perform in hypohydrated and food-deprived states 30 32. Others have suggested that this adaptation could be related to an attenuation in glycogen depletion accompanying food deprivation during weight loss, to an increased rate of glycogen resynthesis accompanying re-feeding during the recovery period or to differences in the rate of glycogen usage during exercise after weight loss 25.…”
Section: Discussionmentioning
confidence: 99%
“…Arabaci and Canakya (2000) investigated the effects of the training program on some physiological parameters in young wrestlers and have reported significant increase in the strength, aerobic capacity, flexibility and the anaerobic power of the wrestlers who regularly participate in the preparation period compared to those who received no training [1]. Buford et al (2006) have studied the impact of competition season on body weight, hydration and muscle performance of college wrestlers. They have reported significant increase in body weight and muscular performance of wrestlers at the end of competition season [5].…”
mentioning
confidence: 99%
“…Buford et al (2006) have studied the impact of competition season on body weight, hydration and muscle performance of college wrestlers. They have reported significant increase in body weight and muscular performance of wrestlers at the end of competition season [5]. In another study, Buford et al (2008) have reported that 2.9 % increase in the amount of body fat before and after the season [6].…”
mentioning
confidence: 99%